Effect of Al2O3 addition to an internal combustion engine coolant on heat transfer performance - Karagoz, Yasin; Koten, Hasan; Tuncer, Erdal; Pusat, Saban (ELSEVIER, 2022)
In vehicle cooling radiators, in general, water is used as a cooling fluid. Adding of nanoparticles to the cooling water has a significant effect on heat transfer performance of the radiator. One of the most popular nanoparticle for this kind of applications is Al2O3. There are some critical issues for the application of nanofluids as homogeneity of nanoparticle distribution and concentration of nanoparticles. In the present study, the Al2O3 particles used in an internal combustion engine cooling radiator to enhance heat transfer performance. The experimental works were done for different concentrations as 0.25, 0.50 and 1.0 wt% and engine brake power values. The enhancement of the heat transfer performance is achieved up to 37.2% (9.4 kW brake power and 1% concentration). The lowest overall heat transfer improvement was obtained as 2% (11.5 kW brake power and 0.25% concentration). The obtained results showed that adding of nanoparticles to the cooling water improves the heat transfer performance.
Keywords: Heat transfer improvement; Nanoparticle; Nanofluid; Al2O3; Vehicleradiator; THERMAL-CONDUCTIVITY; Thermodynamics